Evaluation of newborns hospitalized in the neonatal Intensive Care Unit of the municipal hospital of Governador Valadares, Minas Gerais (Research, Society and Development, 2020)
Pre-term newborns are those newborns with a gestational age of less than 37 weeks of gestation and represent the main population served in neonatal units. This group is variable and has diverse physiological characteristics. The objective of this study was to evaluate the information of preterm newborns in Governador Valadares, Minas Gerais. A descriptive study was carried out based on primary data of newborns collected from the medical records of 279 patients at the neonatal Intensive Care Unit and Progressive Care Unit from September / 2010 to August / 2011 at the public hospital of Governador Valadares. Most newborns were hospitalized from 1 to 20 days (62.4%). Of the pre-term newborns of 23/24 weeks of gestational age, 100% died. Newborns at 25/26 weeks of gestational age had a death rate of 85.7% and 27/28 weeks, 44.4%. The mortality rate decreased to 14.3% among newborns at 39/40 weeks of gestational age, increasing to 23.1% in newborns at 41/42 weeks. Regarding birth weight, the highest death rate was registered in newborns weighing less than 1000 grams (73.4%). Of the 279 patients, 184 had birth weight below 2500 grams, demonstrating that low birth weight characterized the majority of the studied population. 78% of newborns admitted to the Neonatal Intensive Care Unit remained for up to 30 days with a predominance of children between 1,500 and 2,500 grams at birth. There were no significant correlations between gestational age, birth weight and days of hospitalization.